2023
DOI: 10.1609/icwsm.v17i1.22138
|View full text |Cite
|
Sign up to set email alerts
|

Non-polar Opposites: Analyzing the Relationship between Echo Chambers and Hostile Intergroup Interactions on Reddit

Abstract: Previous research has documented the existence of both online echo chambers and hostile intergroup interactions. In this paper, we explore the relationship between these two phenomena by studying the activity of 5.97M Reddit users and 421M comments posted over 13 years. We examine whether users who are more engaged in echo chambers are more hostile when they comment on other communities. We then create a typology of relationships between political communities based on whether their users are toxic to each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Operationalizing Tajfel’s theories in the case of Reddit, Kumar et al (2018) indeed found that subreddits were more likely to engage in conflict when they overlapped in cultures or interests. The authors attributed this to Redditors desiring to attain “positive distinctiveness” (Tajfel & Turner, 1986, p. 23) within the subreddit’s ingroup through displaying aversion toward similar subreddits, forming a type of an intra-platform differentiation that has also been related to “echo chambers” and political polarization online (see also Efstratiou et al, 2022; Marchal, 2020). Similarly, 4chan has also known ample on-site friction between overlapping subgroups, for instance when My Little Pony -fans overwhelmed discussion on /co/ “Comics & Cartoons,” aggravated the community, and eventually split off with the dedicated “/mlp/” board (Erasmus, 2019).…”
Section: Differentiation Despite Connectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…Operationalizing Tajfel’s theories in the case of Reddit, Kumar et al (2018) indeed found that subreddits were more likely to engage in conflict when they overlapped in cultures or interests. The authors attributed this to Redditors desiring to attain “positive distinctiveness” (Tajfel & Turner, 1986, p. 23) within the subreddit’s ingroup through displaying aversion toward similar subreddits, forming a type of an intra-platform differentiation that has also been related to “echo chambers” and political polarization online (see also Efstratiou et al, 2022; Marchal, 2020). Similarly, 4chan has also known ample on-site friction between overlapping subgroups, for instance when My Little Pony -fans overwhelmed discussion on /co/ “Comics & Cartoons,” aggravated the community, and eventually split off with the dedicated “/mlp/” board (Erasmus, 2019).…”
Section: Differentiation Despite Connectednessmentioning
confidence: 99%
“…Less attention has been paid to cross-site relations between comparably subcultural spaces. Several studies have dealt with “internal” conflicts between subreddits (e.g., Buozis, 2021; Efstratiou et al, 2022; Marchal, 2020), while other texts have touched on 4chan’s “symbiotic” relationship with Tumblr (Beran, 2019; Hagen, 2023). Yet the 4chan–Reddit rivalry has only attracted sparse scholarly attention, even though it marks a historically significant online linkage, as I will go on to show (for exceptions, see Donovan et al, 2022; Gallagher & Topinka, 2023; Trammell, 2014).…”
Section: Introductionmentioning
confidence: 99%